Rheological Study of Poly(lactic) Acid Nanocomposites with Carbon Nanotubes and Graphene Additives as a Tool for Materials Characterization for 3D Printing Application - Ivanova Radost (Applied Rheology, 2018)
In the last decades, one of the most critical issues concerning the control on the processing, structure and properties of nanocomposites is related to the dispersion of nanofiller in the polymer matrix and internal interactions resulting in percolation. In this study, we investigate the rheological behavior in oscillatory and steady shear flow of poly(lactic) acid based nanocomposites incorporating 0 – 12 wt% graphene nanoplates (GNP) and multi-walled carbon nanotubes (OH-MWCNT). The effect of the filler contents and aspect ratio on the viscosity and viscoelastic response is evaluated. Three rheological techniques are used for estimation of rheological percolation threshold. Due to different aspect ratio and state of dispersion of GNP and MWCNTs the percolation threshold differs significantly for both compositions ϕp ≤ 1.5 wt% for MWCNT/PLA and ϕp ≤ 5 wt% for GNP/PLA. The larger the aspect ratio of nanofiller, the lower is the rheological percolation threshold. The visualized structure by TEM analysis confirms the rheological predictions for both type composites. The index of flow was estimated by the power law slope of the flow curves and a better dispersion was assumed for MWCNTs in comparison with GNPs due to the surface modification. Based on the rheological percolation threshold and the flow index, nanocomposites were classified in three groups: Newtonian, percolated composites and elastic solids. Both characteristics are used to select the printing parameters for the three groups of nanocomposites, suitable for fused deposition modeling (FDM).